Chromosome abnormalities and genetic counseling - Gardner, R. J. M. (Oxford monographs on medical genetics, 2012)
Chromosome abnormalities have been known for over 50 years, though the methods of analysis have become increasing more sophisticated and precise. Surprisingly, the questions that parents and families raise in genetic counseling have changed little over that period. Questions like, "Why did an abnormality happen? Why did it cause the problems we see in our child? Would it happen again in a future child? How could we avoid it happening again?" are common concerns for families. This new edition of Chromosome Abnormalities and Genetic Counseling deals with these universal questions, and in the con.